Opportunities for collaboration: the synergy between antimicrobial and diagnostic stewardship in pediatrics - Brandy M. Hoyt; Kevin Messacar; Anna C. Sick-Samuels; Preeti Jaggi; Stacey L. Hamilton; Sarah Janelle; Sarah K. Parker (Antimicrobial Stewardship & Healthcare Epidemiology)
Advancement of antimicrobial stewardship (AS) programs requires partnership with clinicians, quality assurance teams, and laboratorians. Inevitably, AS programs also practice diagnostic stewardship (DS), as stewards are aptly placed to connect key stakeholders and help steer processes toward higher value care for pediatric patients. In this review, we illustrate five moments of collaboration between stakeholders in the interplay between AS and DS in pediatrics. These moments include (1) Observation, (2) Reflection, (3) Exploration, (4) Enactment and (5) Evaluation. We offer a targeted narrative of examples in current literature using common relatable scenarios (ie, endotracheal aspirates, blood cultures, gastrointestinal samples, and urine testing) including impact on financial and environmental waste.